GBA3: a polymorphic pseudogene in humans that experienced repeated gene loss during mammalian evolution - Lopes-Marques, Monica (Sci Rep, 2020)
The gene encoding the cytosolic β-glucosidase GBA3 shows pseudogenization due to a truncated allele (rs358231) that is polymorphic in humans. Since this enzyme is involved in the transformation of many plant β-glycosides, this particular case of gene loss may have been influenced by dietary adaptations during evolution. In humans, apart from the inactivating allele, we found that GBA3 accumulated additional damaging mutations, implying an extensive GBA3 loss. The allelic distribution of loss-of-function alleles revealed significant differences between human populations which can be partially related with their staple diet. The analysis of mammalian orthologs disclosed that GBA3 underwent at least nine pseudogenization events. Most events of pseudogenization occurred in carnivorous lineages, suggesting a possible link to a β-glycoside poor diet. However, GBA3 was also lost in omnivorous and herbivorous species, hinting that the physiological role of GBA3 is not fully understood and other unknown causes may underlie GBA3 pseudogenization. Such possibility relies upon a putative role in sialic acid biology, where GBA3 participates in a cellular network involving NEU2 and CMAH. Overall, our data shows that the recurrent loss of GBA3 in mammals is likely to represent an evolutionary endpoint of the relaxation of selective constraints triggered by diet-related factors.